Upaya Perlindungan HKI yang Terkait dengan GRTKF di Tingkat Nasional dan Internasional: Upaya yang Belum Sebanding - Sardjono, Agus (Indonesian Journal of International Law, 2005)
Indonesia is often referred as the fifth largest country that having Intellectual Property Rights (IPR) infringements, it does however not necessarily make Indonesia as a state that does not protect IPR, since Indonesia does have several major laws on IPR protections. The fact has shown on the other hands that the developed nations are not sterile from misappropriation of those IPRs that are primarily corresnponded to the interest of developing countries such as “Genetic Resources, Traditional Knowledge and Folklore”. The conventional concept of IPR is considered unable to deliver the protection for Genetic Resources, Traditional Knowledge, and Folklore (GRTKF) because of its individualist nature. Therefore, it is highly expected there could be a better protection toward GRFTK. This paper will extract the IPR concept related to GRTKF, especially the condition in Indonesia as one of the developing country that has many interests in having protection on GRTKF.